Evaluation of sediment toxicity in different Portuguese estuaries: ecological impact of metals and polycyclic aromatic hydrocarbons - Serafim, M.A. (2020)
Estuaries are exposed to multiple sources of different pollutants which tend to be trapped in sediments. Estuarine sediments can become reservoirs of contaminants that under certain circumstances may be released back to the water column, increasing their availability to the biota. Therefore, assessing sediment quality, of which toxicity testing is one of the lines-of-evidence, is a key element in ecological risk assessment strategies for these ecosystems. The use of Vibrio fischeri as luminescence bacteria is particularly effective in evaluating contaminated sediment. In this study, the ecotoxicity of sediments from five Portuguese estuaries (Aveiro, Tejo, Sado, Mira and Guadiana), was evaluated with a bioassay considering the 50% bioluminescence reduction of V. fischeri bacterium (EC50). Also, the levels of metals and polycyclic aromatic hydrocarbon contaminants (PAHs) were determined in the same sites. Moreover the Sediment Quality Guideline Quotient index (SQG-Q) was assessed for all sediments. The EC50 values varied significantly between estuaries but were strongly correlated with the metal concentrations in the different sites. In general Tejo estuary show higher toxicity levels compared to the other estuaries (5-min EC50 values of 5.6 mg mL(-1)). The integration of sediment contamination data shows that regarding the metallic contamination all sites are moderately impacted, with a higher SQG-Q in the Tejo estuary. On the other hand, when this index is applied to the PAHs levels, all sites are considered unimpacted. This suggests that metal contaminants are the most significant cause of toxicity in these sediments. Nevertheless, other factors can be relevant for this outcome due to the geochemical complexity of estuarine sediments (which affects contaminant speciation and bioavailability) and probably the presence of multiple xenobiotics in these sediments. (c) 2013 Elsevier Ltd. All rights reserved.